Turbo Diesel Engine Exhaust: Advancement at the cost of health –A Review (International Journal of Engineering and Computer Science, 2016)
Technology and advancement are two sides of the same coin, with one comes the other into play. We are living in advanced world leading to development, progressing at a higher pace and with this advancement, we have invited problems for ourselves .With the enhancement in lifestyle, living standard leads to population explosion which consequently leads to increase in number of transportation vehicles. Increase in transportation vehicles are sign of development but on the other hand this rapid increase also leads to problems like pollution, traffic, exploitation of resources. These vehicles include cars, buses, ships, bikes, trains etc. All of these transportation vehicles derive their power from engines. As of the transforming technologies, the engines have also been updated but till now there is no engine which has 100% efficiency. According to thermodynamics any system should give an output as corresponding to the given input. But due to the lack of efficiency the output is as “power with exhaust”. The exhaust is the prominent problem which contributes to pollution. The engines used in cars are internal combustion engine or IC engines. The main pollutant of IC engines are CO, NOx (derivatives of Nitrogen Oxide), partially burned hydro-carbons (HC), particulate matter etc. These pollutants affect our body both directly and indirectly. The problems like Green House Effect and Global Warming are also into play because of the effects of exhaust pollution